2021
DOI: 10.3390/mi12010098
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Recordings of Transmembrane hERG Channel Currents Based on Solvent-Free Lipid Bilayer Microarray

Abstract: The reconstitution of ion-channel proteins in artificially formed bilayer lipid membranes (BLMs) forms a well-defined system for the functional analysis of ion channels and screening of the effects of drugs that act on these proteins. To improve the efficiency of the BLM reconstitution system, we report on a microarray of stable solvent-free BLMs formed in microfabricated silicon (Si) chips, where micro-apertures with well-defined nano- and micro-tapered edges were fabricated. Sixteen micro-wells were manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In previous studies, we used micro-fabricated Si chips as membrane supports to form BLMs and applied them to producing biosensors and light sensing devices. 10,17,21 On the other hand, Teon lms have traditionally been used as a support for BLMs in functional analyses of ion channel activities. 6,22,23 In this study, we developed suitable processes for fabricating electrodes on these Teon lms and Si chips.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we used micro-fabricated Si chips as membrane supports to form BLMs and applied them to producing biosensors and light sensing devices. 10,17,21 On the other hand, Teon lms have traditionally been used as a support for BLMs in functional analyses of ion channel activities. 6,22,23 In this study, we developed suitable processes for fabricating electrodes on these Teon lms and Si chips.…”
Section: Methodsmentioning
confidence: 99%
“…6(a)], enable extremely stable aperture-suspended bilayers, as quantified by aspiration cycles, centrifugal force, large changes to the applied potential and by bilayer lifetime. 9) Recently, a 4 × 4 array of shaped apertures was reported by Miyata et al 32) As illustrated in Fig. 6, a vertically oriented holder for 16 aperture chips was initially flanked by two aqueous compartments of 1.4 ml volume.…”
Section: Parallel Platformsmentioning
confidence: 99%
“…Current recordings of the 16 bilayers were obtained with a 16-channel patch clamp amplifier, with a vertical common ground electrode in the shared trans compartment. 32) Despite the associated mechanical and electrical perturbations, 13 bilayers were formed on average. Miyata et al typically observed hERG ion channel activity, in 120 mM KCl at −100 mV, in six bilayers simultaneously.…”
Section: Sc0804mentioning
confidence: 99%
See 2 more Smart Citations